A STAT6 Intronic Single-Nucleotide Polymorphism is Associated with Clinical Malaria in Ghanaian Children - Amoako-Sakyi, Daniel (Genet Epigenet, 2016)
Malaria pathogenesis may be influenced by IgE responses and cytokine cross-regulation. Several mutations in the IL-4/STAT6 signaling pathway can alter cytokine cross-regulation and IgE responses during a Plasmodium falciparum malarial infection. This study investigated the relationship between a STAT6 intronic single-nucleotide polymorphism (rs3024974), total IgE, cytokines, and malaria severity in 238 Ghanaian children aged between 0.5 and 13 years. Total IgE and cytokine levels were measured by ELISA, while genotyping was done by polymerase chain reaction-restriction fragment length polymorphism (RFLP). Compared with healthy controls, heterozygosity protected against clinical malaria: uncomplicated malaria (odds ratios [OR] = 0.13, P < 0.001), severe malarial anemia (OR = 0.18, P < 0.001), and cerebral malaria (OR = 0.39, P = 0.022). Levels of total IgE significantly differed among malaria phenotypes (P = 0.044) and rs3024974 genotypes (P = 0.037). Neither cytokine levels nor IL-6/IL-10 ratios were associated with malaria phenotypes or rs3024974 genotypes. This study suggests a role for rs3024974 in malaria pathogenesis and offers further insights into an IL-4/STAT6 pathway mutation in malaria pathogenesis.